Radiological analysis of 40K, 226Ra and 232Th in fish, crustacean and sediment samples from fresh and marine water in oil exploration area of Ondo State, Nigeria (2010)
Radiological analysis was carried out on fish, crustacean and sediment samples collected from both fresh and marine water of river Igbokoda in the coastal area of Ondo State, Nigeria. The activity concentrations of radionuclides were determined using gamma spectrometry method. The means of the annual effective ingestion dose varied between 23.3 ± 10.2μSv.y-1 (OreochromisniloticusandGymnarchusniloticus) and 34.8 ± 1.7 μSv.y-1 (Parachnnaobscura) for fresh water fish samples and 6.4 ± 0.7 μSv.y-1 (Chrysithctysnigrodigitatus)and14.2 ± 1.6 μSv.y-1 (Cynoglossussenegalensis) for marine water fish samples. That of the crustacean samples (Peanusmonodon) was 2.4 ± 0.2 μSv.y-1. The equivalent dose to the skin of humans from contact with sediment was 2.0 μSv.y-1 and 1.2 μSv.y-1 for the fresh and marine water sediments, respectively. The effective dose was calculated as 0.010 μSv.y-1 and 0.006 μSv.y-1 for the fresh and marine water sediments, respectively. The equivalent doses obtained are less than the ICRP recommended 50mSv per annum for the public.